Emission of particulate matter from a desktop three-dimensional (3D) printer - Yi, Jinghai; LeBouf, Ryan F.; Duling, Matthew G.; Nurkiewicz, Timothy; Chen, Bean T.; Schwegler-Berry, Diane; Virji, M. Abbas; Stefaniak, Aleksandr B. (Journal of Toxicology and Environmental Health, Part A, 2016)
Desktop three-dimensional (3D) printers are becoming commonplace in business offices, public libraries, university labs and classrooms, and even private homes; however, these settings are generally not designed for exposure control. Prior experience with a variety of office equipment devices such as laser printers that emit ultrafine particles (UFP) suggests the need to characterize 3D printer emissions to enable reliable risk assessment. The aim of this study was to examine factors that influence particulate emissions from 3D printers and characterize their physical properties to inform risk assessment. Emissions were evaluated in a 0.5-m 3 chamber and in a small room (32.7 m 3 ) using real-time instrumentation to measure particle number, size distribution, mass, and surface area. Factors evaluated included filament composition and color, as well as the manufacturer-provided printer emissions control technologies while printing an object. Filament type significantly influenced emissions, with acrylonitrile butadiene styrene (ABS) emitting larger particles than polylactic acid (PLA), which may have been the result of agglomeration. Geometric mean particle sizes and total particle (TP) number and mass emissions differed significantly among colors of a given filament type. Use of a cover on the printer reduced TP emissions by a factor of 2. Lung deposition calculations indicated a threefold higher PLA particle deposition in alveoli compared to ABS. Desktop 3D printers emit high levels of UFP, which are released into indoor environments where adequate ventilation may not be present to control emissions. Emissions in nonindustrial settings need to be reduced through the use of a hierarchy of controls, beginning with device design, followed by engineering controls (ventilation) and administrative controls such as choice of filament composition and color.